Cambridge English IELTS 11 general training with answers authentic examination papers (Cambridge Cambridge University Press, 2016)
Authentic examination papers from Cambridge Assessment English provide perfect practice because they are EXACTLY like the real test.
Keywords: English language; IELTS; Textbooks for foreign speakers; English language - Examinations; questions International; English Language Testing System - Study guides